Analysis of Injuries in Athletes Practitioners Amateur Race Street (Research, Society and Development, 2020)
The injuries that involve the sports world are caused by rigidity in training and competitions, these are classified according to the mechanism and the affected region. The biotype of each athlete varies, being visible via some coefficients such as sex, age, flexibility and muscle strength. To analyze the most common types of injuries in street athletes, to compare sex, age, flexibility and muscle strength to the following coefficients, and to investigate sociodemographic aspects of practitioners.: In the event promoted by the Association of Street Runners of Rio Grande (ACORRG), fourteen athletes were submitted to a questionnaire about their training habits containing thirteen questions and two tests, one of flexibility, test of Wells bench, another of muscular strength, 1RM test. The results showed muscle strain and tendinopathy as the main conditions and stood out in the female sex with six of seven volunteers, reaching the standard of excellence in flexibility. Balance was predominant in muscle strength, with no significant difference between genders. The relationship between flexibility and muscle strength shows female overcoming in both values. Conclusion: The influence of muscle strength and flexibility resulted in an influential and decisive relationship in the formation of injuries, because in women where the values were considered positive, the number of athletes without injury was greater.